Metabolic reprogramming as a therapeutic target for modulating the Th17/Treg balance in autoimmune diseases: a comprehensive review - Hu, Yuehong; Zhao, Qihan; Dai, Haoran; Wu, Yadi; Tang, Xinyue; Zhang, Naiqian; Jiang, Hanxue; Rui, Hongliang; Liu, Baoli (Frontiers in Immunology, 2025)
The dynamic balance between T helper 17 (Th17) cells and regulatory T (Treg) is the cornerstone of immune homeostasis. Disruption of this equilibrium is closely associated with various autoimmune diseases, including rheumatoid arthritis (RA), multiple sclerosis (MS), and inflammatory bowel disease (IBD). Studies have revealed that metabolic reprogramming, mediated by key metabolic enzymes (including mTOR, HIF-1α, and AMPK) and pathways (such as glycolysis and lipid metabolism), acts as a major regulator of Th17/Treg differentiation and function owing to their distinct metabolic profiles. Metabolic dysregulation may exacerbate immune imbalance by altering the cellular differentiation trajectories and functional states. Although targeting metabolic pathways shows therapeutic promise, current intervention strategies face challenges in terms of specificity and safety. This review systematically combs the mechanisms by which metabolic reprogramming influences the differentiation and function of Th17/Treg cells, as well as the metabolic changes in immune cells of inflammation-related autoimmune diseases. It outlines the progress of the latest metabolism-targeted strategies and focuses on discussing the challenges and prospects regarding the specificity and safety of metabolic interventions.